Volumetric analysis of the aging auditory pathway using high resolution magnetic resonance histology - Du, Eric Y.; Ortega, Briana K.; Ninoyu, Yuzuru; Williams, Robert W.; Cofer, Gary P.; Cook, James J.; Hornburg, Kathryn J.; Qi, Yi; Johnson, G. Allan; Friedman, Rick A. (Frontiers in Aging Neuroscience, 2022)
Numerous shown consequences of age-related hearing loss have been unveiled; however, the relationship of the cortical and subcortical structures of the auditory pathway with aging is not well known. Investigations into neural structure analysis remain sparse due to difficulties of doing so in animal models; however, recent technological advances have been able to achieve a resolution adequate to perform such studies even in the small mouse. We utilize twelve members of the BXD family of recombinant inbred mice and aged separate cohorts. Utilizing novel magnetic resonance histology imaging techniques, we imaged these mice and generated high spatial resolution three dimensional images which were then comprehensively labeled. We completed volumetric analysis of twelve separate regions of interest specific to the auditory pathway brainstem nuclei and cortical areas with focus on the effect of aging upon said structures. Our results showed significant interstrain variation in the age-related effect on structure volume supporting a genetic influence in this interaction. Through multivariable modeling, we observed heterogenous effects of aging between different structures. Six of the twelve regions of interests demonstrated a significant age-related effect. The auditory cortex and ventral cochlear nucleus were found to decrease in volume with age, while the medial division of the medial geniculate nucleus, lateral lemniscus and its nucleus, and the inferior colliculus increased in size with age. Additionally, no sex-based differences were noted, and we observed a negative relationship between auditory cortex volume and mouse weight. This study is one of the first to perform comprehensive magnetic resonance imaging and quantitative analysis in the mouse brain auditory pathway cytoarchitecture, offering both novel insights into the neuroanatomical basis of age-related changes in hearing as well as evidence towards a genetic influence in this interaction. High resonance magnetic resonance imaging provides a promising efficacious avenue in future mouse model hearing loss investigations.